Bioaugmentation of Methanosarcina thermophila grown on biochar particles during semi-continuous thermophilic food waste anaerobic digestion under two different bioaugmentation regimes. (September 2022) - Lee, Jonathan T.E.; Dutta, Nalok; Zhang, Le; Tsui, Thomas T.H.; Lim, Shuhan; Tio, Zhi Kai; Lim, Ee Yang; Sun, Jiachen; Zhang, Jingxin; Wang, Chi-Hwa; Ok, Yong Sik; Ahring, Birgitte K.; et al.
Graphical abstract: Highlights: Bioaugmentation of Methanosarcina thermophila was performed with growth on biochar. Single dose of bioaugmentation was compared with a routine regime (split into 10). Both types of dosing performed better than their controls in terms of methane yield. The best Routine reactor showed 37% more yield, while the best Single presented 32%. Overall, Single dose was better than Routine condition for mean methane production. Abstract: This study presents the effect of bioaugmentation of thermophilic anaerobic digestion of food waste with Methanosarcina thermophila grown on a wood-derived biochar. Two different supplementation regimes were tested, namely a single bioaugmentation (SBABC) in which 10% v/v of the microbes grown on biochar (1 g/L) is added at setup of the reactors, versus a routine bioaugmentation (RBABC) wherein the same amount of supplements were added over 10 feeding cycles. The optimally performing 'R' and 'S' reactors had increased methane yields by 37% and 32% over their respective controls while reactors SBABC 2 and 3 produced 21.89% and 56.09% higher average methane yield than RBABC 2 and 3, respectively. It appears that a single dose bioaugmentation is advantageous for improving AD as analysed in terms of average methane yield and VFA production. This study provides the basis for understanding how biochar and bioaugmentation can be used for engineering sustainable pilot-scale AD processes.